Directed Growth of Electroactive Metal‐Organic Framework Thin Films Using Electrophoretic Deposition. (28th July 2014) - Hod, Idan; Bury, Wojciech; Karlin, David M.; Deria, Pravas; Kung, Chung‐Wei; Katz, Michael J.; So, Monica; Klahr, Benjamin; Jin, Danni; Chung, Yip‐Wah; Odom, Teri W.; Farha, Omar K.; et al.
<x xml:space="preserve">Abstract</x> Electrophoretic deposition (EPD) is used to assemble metal–organic framework (MOF) materials in nano‐ and micro‐particulate, thin‐film form. The flexibility of the method is demonstrated by the successful deposition of 4 types of MOFs: NU‐1000, UiO‐66, HKUST‐1, and Al‐MIL‐53. Additionally, EPD is used to pattern the growth of NU‐1000 thin films that exhibit full electrochemical activity. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>